Representations of the generalization of a functional relationship and the relation with the interviewer’s mediation - Ureña Alpízar, Jason de Jesús (2019)
The ability to generalize and represent generalizations exhibited by eight fourth-grade students was analysed in this descriptive study, designed around a semi-structured interview involving a task based on the linear functional relationship y = x + 2. The relation of the interviewer’s mediation on students’ representations of generalizations was determined on the grounds of students’ interactions with her. Four forms to represent the generalization of a functional relationship were defined. The findings confirm the importance of mediation in helping students strengthen their ability to recognize, represent and generalize functional relationships.